Green synthesis of silver nanoparticles using Indigofera cordifolia leaf extract and their pharmacological potential - Siva, P. K.; Sathish, M.; Parvathi, T.; Kamaraj, M.; Bhuvaneswari , R.; Arumugam, M. (Journal of Phytology, 2021)
Biologically the silver nanoparticles were synthesized from Indigofera cordifolia leaves extract. The absorbance of the silver nanoparticles centered at four hundred and twenty nm, with respect to the surface plasmon resonance of silver nanoparticles wavelength. XRD method proves, biosynthesized NPs would retain the face centered cubic (fcc) structure. In TEM image analysis, silver NPs morphology was spherical in shape. The composition of the silver nanoparticles was obtained by EDAX analysis method. FTIR analysis concluded that biosynthesis Ag NPs was observed at 1384 cm-1, with respect to –NO3 stretching arises from AgNO3. Ten types of bands are present in the broad emission because of organic matrix bound to silver nanoparticles, which reveals as the result of photoluminescence measurements. The silver NPs possess more antibacterial activity as compared to the standard drug, Amoxicillin.